Pemanfaatan Batu Sungai Laeya Kabupaten Konawe Selatan sebagai Campuran Stone Matrix Asphalt Halus - Galantono Manggasa; Alpius; Elizabeth (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The development of transportation is increasingly advanced in the world so that there are many vehicles that cross the highway so that the quality of road pavement needs to be improved. This study was intended to determine the quality of the Laeya river stone, Konawe Selatan Regency, in a fine mixture of stone matrix asphalt (SMA). The method used in this study is to test the characteristics of the aggregate and then design the composition of the fine stone matrix asphalt (SMA) mixture as well as the conventional Marshall test and the Marshall immersion test. The research results concluded that the aggregate originating from the Laeya river met the requirements as a material used in road pavement. From the results of the conventional marshall test using asphalt content of 6.00%, 6.25%, 6.50%, 6.75%, 7.00% the values ​​for stability, VIM, flow, VMA were obtained which met the general specifications of the 2018 Highways. From the marshall immersion test, the residual marshall stability value was obtained at 98.54% with an asphalt content of 7.00% and met the specified standards, namely at least > 90%.